2019
DOI: 10.1186/s12886-019-1040-2
|View full text |Cite
|
Sign up to set email alerts
|

Open globe and penetrating eyelid injuries from fish hooks

Abstract: BackgroundA few case reports have described accidental eye injuries caused by fish hooks. The severity of ocular injuries is dependent on the involved ocular structures. Severe ocular injuries due to fish hooks are rare. We describe open globe and penetrating eyelid injuries from fish hooks at the Baltic Sea.MethodsNine patients with traumatic ocular injuries caused by fish hooks were included. The following parameters were evaluated: severity of injury, best corrected visual acuity at admission and last follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…In cut-it-out technique, the primary wound is enlarged and the hook is removed by backing through the same wound. [6][7][8][9][10][11] Fish hooks can also cause perforating injuries to the eye and these can be distinguished by the presence of entry and exit wounds. Management of these cases should be done cautiously to avoid further injury to the delicate ocular tissues as the hook is removed.…”
Section: Discussionmentioning
confidence: 99%
“…In cut-it-out technique, the primary wound is enlarged and the hook is removed by backing through the same wound. [6][7][8][9][10][11] Fish hooks can also cause perforating injuries to the eye and these can be distinguished by the presence of entry and exit wounds. Management of these cases should be done cautiously to avoid further injury to the delicate ocular tissues as the hook is removed.…”
Section: Discussionmentioning
confidence: 99%
“…In the fishing industry and in sports fishing, injury can occur when fishing hooks, lures, rod tips, or lines accidentally strike the eye [ 161 , 162 , 163 , 164 ]. Any eye structure may be involved with damage ranging from corneal abrasion to penetrating injury to globe rupture.…”
Section: Workplace Ocular Injuriesmentioning
confidence: 99%
“…Purtskhvanidze et al [2] reported nine patients who experienced eye injury caused by fishhook. Five patients had only eyelid injury (55%) and four patients suffered open globe injuries (45%).…”
Section: Case Reportmentioning
confidence: 99%